Portretten en een oude droom van Kader Abdolah: Een etnisch gekleurde autobiografie en de ethische dimensie van het identiteitsvormingsproces - Dynarowicz, Ewa (Zakład Studiów Niderlandzkich i Południowoafrykańskich, Wydział Anglistyki UAM / Wydawnictwo Naukowe Exemplum, 2006)
Two problems are central to Kader Abdolah’s Portretten en een oude droom [Portraits and an Ancient Dream]: firstly, his Persian background and the problem of migration, secondly, coping with a sense of guilt. This article examines the novel’s autobiographical character as reflecting upon the identity-forming process of an emigrant. It especially focuses on narrative techniques used to depict the complexity of this process and on the role of the Other in creating one’s self-image. The second section of the article is devoted to the ethical dimension of a particular identity and the problem of reconciliation with oneself. The reading strategy applied to analyse this aspect of Abdolah’s novel takes the philosophy of Paul Ricoeur as presented in Soi-meme comme un autre as a central point of departure.